STRENGTHENING STUDENT TOLERANCE THROUGH INTERNALIZING THE VALUES OF RELIGIOUS MODERATION IN SCHOOLS - Dede Setiawan; Restiana Abelia; Saiful Bahri (Nurul Jadid University, 2025)
Religious moderation is a priority of Indonesian education policy because of the intolerance and likely social conflict over numerous religious identities. In addition to knowledge transfer, schools also teach pupils tolerance, openness, and respect for differences. This study will discuss the absorption of the ideas of religious moderation to increase tolerance in the classroom and develop religion-based character education. The design of this qualitative study was a case study. Observation and documentation supplemented semi-structured interviews with five teachers and ten pupils. Data reduction, presentation and conclusion were made by interactive theme analysis approach. The results indicated that classroom instruction, teacher role models, inclusive school culture, and character-building activities such as Anti-Violence Ambassadors could assist kids to internalize religious moderation. The results indicate that children comprehend religious moderation and can apply it in social interactions at school. Therefore, religious moderation in school learning and culture provides a tolerant, harmonious, and inclusive educational atmosphere and enhances the character education model that can be duplicated in other Indonesian schools.